Katakumby monasteru supraskiego - Mironowicz, Antoni (Elpis, 2022)
The bodies of the founders and representatives of many prominent Orthodox families from the Grand Duchy of Lithuania were buried in the catacombs of the Suprasl monastery in the 16th century. Some of the people buried in the catacombs were transferred to the altar part of the Church of the Annunciation of the Blessed Virgin Mary in 1644. Currently, an important problem is the protection and reconstruction of the Suprasl catacombs.